IFPRI and the European Commission: Partnering towards food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
On June 15-16, 2016, the European Commission (EC) will host the 10th European Development Days (EDD) to bring the development community together to share ideas and experiences in ways that will inspire innovative solutions and new partnerships that address the world’s most pressing challenges. To engage the development community in accelerating progress towards food and nutrition security, IFPRI, Concern Worldwide, the Technical Centre for Agricultural and Rural Cooperation (CTA), and Welthungerhilfe are organizing a session during the EDD on “Ending Hunger and Undernutrition: It can be done faster.” Preceding the EDD, IFPRI together with the EC and other partners, will hold an event on June 14 on “Going the Last Mile: Accelerating Progress in Food Security and Nutrition."